RELIGIOUS PRACTICES OF THE ARMENIANS OF THE ORDUBAD DISTRICT OF THE NAKHICHEVAN ASSR IN THE 1950–1980s - Andreeva, Ulia Olegovna; Gulaeva, Evgenia Ur'evna; Dalalan, Tork (History, Archeology and Ethnography of the Caucasus, 2024)
The article is devoted to the religious practices of Armenians who lived in the 1950s-1980s on the territory of the Ordubad district of the Nakhichevan Autonomous Soviet Socialist Republic. The main task is to introduce new materials into the scientific circulation, a preliminary analysis of which is offered in this article. The research was carried out within the framework of the oral history approach and is based on the materials of interviews with former residents of the Nakhichevan ASSR, who were forced or voluntarily left there in the late Soviet period. Fieldwork was conducted in Armenia and Russia in 2021-2023. Despite the religious persecution in the pre-war time, Armenians continued to identify themselves as Christians, visit holy places, light candles, and celebrate Christian holidays. Most of the informants were not baptized, all rites of the life cycle were limited to civil ceremonies. At the same time, many in one way or another celebrated some religious holidays, and for the residents of the Ordubad district the most significant event of the year was Vardavar (Transfiguration of Jesus). This day was timed to the pilgrimage to holy places, the sacrifice of matagh and the feast. Our interlocutors almost did not tell anything about the persecution or restrictions on participation in religious holidays. Our field material showed that the absence of functioning religious institutions in Nakhichevan led to the fact that religious life shifted to the sphere of domestic and informal.
Keywords: Nakhichivan; Goght’n; Armenians; religion; holy places; religious practices; calendar